2020
DOI: 10.1002/jsfa.10550
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2, temperature and nitrogen levels impact growth and development of invasive weeds in the Mediterranean region

Abstract: BACKGROUND Invasive plant species present a serious threat to the environment, as well as human and animal health. An interaction may exist between the climatic changes and invasive plant species. In this 2‐year study, we investigated the effects of warming, CO2 and nitrogen application on the biomass, growth and leaf tissue nitrogen concentration of three invasive weed species. Treatments were: (i) simulated (elevated) CO2 (approximately 800–900 ppm); (ii) warming or high temperature (day/night 25/15 °C); (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…The results obtained in this study indicate that nitrogen addition significantly increased and warming slightly decreased species’ growth, which was consistent with Jabran and Dogan (2020) who found that invasive weed species were generally negatively or neutrally affected by warming, and weeds mostly had a positive response to nitrogen application. These results may relate to soil fertility and plant phytohormones (e.g., cytokinin and auxin) improved by nitrogen addition ( Tulloss and Cadenasso, 2016 ; Peng et al., 2019 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results obtained in this study indicate that nitrogen addition significantly increased and warming slightly decreased species’ growth, which was consistent with Jabran and Dogan (2020) who found that invasive weed species were generally negatively or neutrally affected by warming, and weeds mostly had a positive response to nitrogen application. These results may relate to soil fertility and plant phytohormones (e.g., cytokinin and auxin) improved by nitrogen addition ( Tulloss and Cadenasso, 2016 ; Peng et al., 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…These results may relate to soil fertility and plant phytohormones (e.g., cytokinin and auxin) improved by nitrogen addition ( Tulloss and Cadenasso, 2016 ; Peng et al., 2019 ). For another, a decrease in CO 2 assimilation (induced by the inactivation of photosynthetic enzymes) and a greater rate of maintenance respiration with the increasing temperature will ultimately reduce plant growth ( Monteith and Moss, 1997 ; Ziska and Bunce, 1998 ; Jabran and Dogan, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…2010; Runion et al . 2016; Jabran & Dagon 2020) show that alien plants will be more invasive under climate change conditions. In general, invasive species present higher phenotypic plasticity than native ones.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive plants grown at elevated [CO 2 ] can increase nitrogen and water use efficiency (Runion et al . 2016), biomass production and growth (Jabran & Dogan 2020). Thus, invasive plants may become more problematic under climate change scenarios (Jabran & Dogan 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation